Mass spectrometry : techniques for structural characterization of glycans - Madson, Michael A. (Amsterdam, Netherlands : Elsevier, 2016)
Mass Spectrometry: Techniques for the Structural Characterization of Glycans presents new methods for conducting detailed carbohydrate qualitative analysis-arming analytical chemists, pharmaceutical scientists, and food scientists with a quick reference that will allow them to determine the structures of carbohydrates molecules. As there is a need in the scientific community for content specific to structural determination and analysis of new glycoprotein drug, and because structure-activity analysis requires a structural determination of the N- and O-linked oligosaccharides linked to glycol-proteins, this book provides the relevant research that are necessary for advances and new outcomes in this area of study.
Title page; Table of Contents; Copyright; Dedication; Mass Spectral Analysis of Carbohydrates; Abstract; 1 Isolation Methods for MS Analysis; 2 Component Monosaccharide Analysis by Acid Catalyzed Hydrolysis of Glycan and Qualitative Chromatographic Identification by HPLC; 3 Identification of Glycoses Versus Glycitols by HPAEC-PAD Difference Chromatograms; 4 The Methods for Preparing an Oligosaccharide Reducing Glycan from a Glycoprotein, Linked Through O-Glycosidic Linkage; Conclusions; References.
Print version record.
Includes bibliographical references.
Keywords: Glycoproteins -- Spectra; Mass spectrometry; SCIENCE -- Life Sciences -- Biochemistry; Mass spectrometry; Glycoproteins -- analysis; Electronic books